2021
DOI: 10.5644/ama2006-124.322
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Clinical Significance of EIF1AX Mutations and Co-Mutations

Abstract: <p><strong>Objective</strong>. Mutations in the EIF1AX gene have been recently detected in a small percentage of benign and malignant thyroid lesions. We sought to investigate the prevalence and clinical significance of EIF1AX mutations and co-mutations in cytologically indeterminate thyroid nodules at our institution.</p><p><strong>Materials and Methods</strong>. A 5-year retrospective analysis was performed on thyroid nodules with a cytologic diagnosis of Bethesda ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…More recently, three groups assessed the pattern of EIF1AX mutations in thyroid cancers. Gargano et al reported, in a series of surgically removed nodules, a risk of malignancy of 100% for specimens with EIF1AX mutations (most of them at A113splice) when coexisting with additional mutations (overwhelmingly at NRAS , HRAS , or KRAS ) ( 63 ). Karsogliu-French and colleagues evaluated 31 consecutive patients with EIF1AX mutations: the 18 specimens without coexisting mutations in RAS genes were enriched in benign disease (12/18 were FA, 3/18 hyperplastic nodules (HN) and 3/18 FTC), whereas the 13 EIF1AX + RAS samples showed primarily malignant phenotypes (6/13 PTC, 3/13 ATC, 2/13 NIFTP, 1/13 FA, and 1/13 HN) ( 64 ).…”
Section: Additional Mutations In Thyroid Cancer Prognosticationmentioning
confidence: 99%
“…More recently, three groups assessed the pattern of EIF1AX mutations in thyroid cancers. Gargano et al reported, in a series of surgically removed nodules, a risk of malignancy of 100% for specimens with EIF1AX mutations (most of them at A113splice) when coexisting with additional mutations (overwhelmingly at NRAS , HRAS , or KRAS ) ( 63 ). Karsogliu-French and colleagues evaluated 31 consecutive patients with EIF1AX mutations: the 18 specimens without coexisting mutations in RAS genes were enriched in benign disease (12/18 were FA, 3/18 hyperplastic nodules (HN) and 3/18 FTC), whereas the 13 EIF1AX + RAS samples showed primarily malignant phenotypes (6/13 PTC, 3/13 ATC, 2/13 NIFTP, 1/13 FA, and 1/13 HN) ( 64 ).…”
Section: Additional Mutations In Thyroid Cancer Prognosticationmentioning
confidence: 99%